PENGARUH TEKNIK MODELING TERHADAP PERILAKU MORAL ANAK USIA 5-6 TAHUN DI TK ASH-SHOFA KECAMATAN KUBU KABUPATEN ROKAN HILIR - Sri Rahayu; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of observation on the moral behavior of students have not developed optimally. So it is necessary to apply the modeling technique. This study aims to determine the effect of modeling techniques on moral behavior of children aged 5-6 years in Ash-Shofa Kindergarten Kubu District Rokan Hilir Regency. The research used experimental method with one group pre-test post-test design design with 18 sample of children. The data collection technique used is observation. Data analysis technique using t-test test by using program SPSS 18.0. From result of data analysis obtained tcount = 20,584 bigger than ttable = 2,110 with Sig 0,000 <0,05. It can be concluded that there are significant differences in moral behavior of students before and after applying modeling techniques. The influence of modeling technique on moral behavior of children aged 5-6 years in Ash-Shofa Kindergarten Kecamatan Kubu Rokan Hilir Regency based on the formula N Gain of 54.27%.Keywords: Moral Behavior, Modeling Technique